Chordomas of the skull base: MR features. - Meyers, S P; Hirsch, W L; Curtin, H D; Barnes, L; Sekhar, L N; Sen, C (American Journal of Neuroradiology, 1992)
PURPOSE To characterize the MR features of skull base chordomas with regard to signal intensity, size, position, extension, and Gd-DTPA enhancement.PATIENTS AND METHODS The MR imaging studies of 28 patients with surgically proven chordomas of the skull base were retrospectively reviewed. Twenty-two of these patients received intravenous administration of Gd-DTPA.RESULTS On short TR/short TE images, chordomas generally had low to intermediate signal. On long TR/long TE images, chordomas generally had very high signal that was heterogeneous in 79%. After Gd-DTPA administration, all chordomas demonstrated some degree of contrast enhancement. In most cases, enhancement was demonstrated throughout most of each tumor in a heterogeneous pattern. Chordomas were associated with MR findings of displacement and encasement of vessels, and frequent extension into adjacent structures such as the cavernous sinus, sella, nasopharynx, and hypoglossal canal.CONCLUSION The MR characterization of the position and extent of these neoplasms played an important role in determining the optimal surgical approaches for gross total tumor resection.